Efek Stresor Rasa Sakit Renjatan Listrik terhadap Limfosit dan Makrofag pada Gingiva Tikus Sprague Dawley (The Effect of Electrical Shock Stressor on Lymphocytes and Macrophages in Gingival Tissue of Sprague Dawley Rats) - Vananda Duanta Kantasa; Banun Kusumawardani; Herniyati . (Pustaka Kesehatan, 2016)
Background: Stress has negative impact for oral health and can cause periodontal disease, because the secretion of cortisol increase when stress occur. The excessive secretion of cortisol assumed to decrease the number of lymphocytes and macrophages in gingiva which play a role on immunity of oral health. Objective: To determine the effect of electrical shock stressor on the number of lymphocytes and macrophages in gingival tissue of Sprague Dawley rats. Methods: Sprague Dawley rats were given electrical shock for 7 days (S1), 14 days (S2), and 28 days (S3). Lymphocytes and macrophages observed on histological preparation in interdental gingiva between first molar and second molar used binocular microscope, 1000x magnification. Result: The results showed that the number of lymphocytes in S1 group (3,67±0,816), S2 (3,83±0,752), and S3 (3,17±0,527), also macrophages in S1 group (0,83±0,752), S2 (1,00±0,894), and S3 (0,67±0,816) were lower than the number of lymphocytes (0,67±0,816) and macrophages (2,00±0,632) in control group. The number of lymphocytes (p = 0,002) and macrophages (p = 0,033 ) had significant difference between groups. Conclusion: The electrical shock stressor decreased the number of lymphocytes and macrophages in gingival tissue of Sprague Dawley rats that could cause the oral cavity risk to periodontal infection.   Keywords: electrical shock stressor, gingiva, lymphocytes, macrophages, stress